Effectiveness of feed additive mixture on performance, gut health and antioxidant status of broiler chicken - Mahfudz, Luthfi Djauhari; Ma’rifah, Binti; Sarjana, Teysar Adi; Maulana, Arif (Journal of Advanced Veterinary Research, 2026)
This study aimed to evaluate the effect of a feed additive mixture of noni (Morinda citrifolia) leaf extract, citric acid, and Lactobacillus acidophilus (NCL) on superoxide dismutase (SOD) levels, malondialdehyde (MDA) levels, duodenal villi height, duodenal crypth depth, and body weight gain. A total of 200 broiler chickens aged 8 days, with an average body weight of 213.875 ± 8.9 g. The experimental design employed a completely randomized design (CRD) with four treatments, five replications, and 10 broilers per replicate (T0: drinking water only; T1: drinking water + 1% feed additive; T2: drinking water + 2% feed additive; T3: drinking water + 3% feed additive). Administration of NCL through drinking water significantly (P<0.05) increased SOD levels by 1% and 2%. The administration of feed additives via drinking water significantly reduced (P<0.05) MDA levels in T2. Treatments T1, T2, and T3 showed significantly higher (P<0.05) villus heights than the control group (T0), while no significant differences (P>0.05) were observed among T1, T2, and T3. The greatest crypt depth was recorded in T2, whereas the smallest crypt depth was noted in T0. The feed additive mixture (NCL) led to a significant increase (P<0.05) in body weight gain of broiler chickens. In conclusion, combined effects of phytobiotics, acidifiers, and probiotics in NCL can be an effective additive feed approach to improve antioxidant status, gut morphology, and growth performance in broiler chickens.